2016
DOI: 10.3171/2016.3.focus15634
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation in intractable pain management: outcomes and predictors of revisions of spinal cord stimulators

Abstract: OBJECTIVE Spinal cord stimulators (SCSs) appear to be safe and efficacious for chronic intractable back pain. Although there are many reports on percutaneous SCSs, there are very few studies on outcomes of paddle lead SCSs. In addition, the predictors of requirement for SCS revision have not been well established. Here, the authors review the outcome of a case series and attempt to identify the predictors of SCS revisions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…Accordingly, a link between obesity and post-operative complications after spinal cord stimulator implantation has been established in the literature. 22,23 Marola et al reported a higher complication rate among patients with BMI > 36.5 in a retrospective review of 77 patients undergoing SCS implantation. 23 Similarly, in a retrospective study of 141 patients undergoing SCS implantation for chronic pain syndrome, Bir et al found that BMI > 30 kg/m 2 was predictive of need for early revision after surgery due to mechanical complications such as hardware malfunction or lead migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a link between obesity and post-operative complications after spinal cord stimulator implantation has been established in the literature. 22,23 Marola et al reported a higher complication rate among patients with BMI > 36.5 in a retrospective review of 77 patients undergoing SCS implantation. 23 Similarly, in a retrospective study of 141 patients undergoing SCS implantation for chronic pain syndrome, Bir et al found that BMI > 30 kg/m 2 was predictive of need for early revision after surgery due to mechanical complications such as hardware malfunction or lead migration.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly, in a retrospective study of 141 patients undergoing SCS implantation for chronic pain syndrome, Bir et al found that BMI > 30 kg/m 2 was predictive of need for early revision after surgery due to mechanical complications such as hardware malfunction or lead migration. 22 These mechanical complications are likely attributable to technical challenges inherent to operating on obese patients, as patient positioning and tissue depth can interfere with lead and generator placement. 23,24 In addition to mechanical complications, high BMI has been linked with increased post-operative infections after spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with this trial process, after permanent implantation, only 48% of patients who receive SCS for FBSS achieved 50% or greater pain relief at long‐term follow‐up visit . Evidence has also shown that higher body mass index (BMI), smoking, and drug use may impede benefits . Psychological factors may also play a role, though individual measures of psychological function have not been reproduced .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is suitable for patients requiring higher amplitudes of stimulation. Recently, the rechargeable pulse generator has been used widely because of its small size and ease of maintenance [14,15].…”
Section: The Equipment and Technologymentioning
confidence: 99%